2020
DOI: 10.1186/s13567-020-00756-2
|View full text |Cite
|
Sign up to set email alerts
|

Porcine circovirus type 2 exploits JNK-mediated disruption of tight junctions to facilitate Streptococcus suis translocation across the tracheal epithelium

Abstract: Porcine circovirus type 2 (PCV2) is considered as the primary pathogen of porcine circovirus-associated disease (PCVAD), which results in significant economic losses worldwide. Clinically, PCV2 often causes disease through coinfection with other bacterial pathogens, including Streptococcus suis (S. suis), and especially the highly prevalent S. suis serotype 2 (SS2). The present study determined that continuous PCV2 infection in piglets down-regulates tight junction proteins (TJ) ZO-1 and occludin in the lungs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Only three in vitro co-infection studies have been performed using different cell types to study S. suis and PCV-2 co-infection (Table 1 ) [ 21 , 99 , 100 ]. The results of the first study, which used poorly characterized immortalized swine tracheal epithelial cells, showed that although no increased adhesion or invasion of S. suis serotype 2 was observed, the virus pre-infection decreased the expression levels of ZO-1 and occludin, increased cell permeability and contributed to the translocation of S. suis serotype 2 across the tracheal epithelium [ 99 ]. Although this in vitro model suggests a possible role of PCV-2 during the initial steps of co-infection by S. suis , the level of replication of PCV-2 in tracheal and other respiratory epithelia in pigs is limited, since PCV-2 infects mainly lymphoblast and monocytes (101).…”
Section: S Suis and Viral Mixed And/or Co-infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only three in vitro co-infection studies have been performed using different cell types to study S. suis and PCV-2 co-infection (Table 1 ) [ 21 , 99 , 100 ]. The results of the first study, which used poorly characterized immortalized swine tracheal epithelial cells, showed that although no increased adhesion or invasion of S. suis serotype 2 was observed, the virus pre-infection decreased the expression levels of ZO-1 and occludin, increased cell permeability and contributed to the translocation of S. suis serotype 2 across the tracheal epithelium [ 99 ]. Although this in vitro model suggests a possible role of PCV-2 during the initial steps of co-infection by S. suis , the level of replication of PCV-2 in tracheal and other respiratory epithelia in pigs is limited, since PCV-2 infects mainly lymphoblast and monocytes (101).…”
Section: S Suis and Viral Mixed And/or Co-infectionsmentioning
confidence: 99%
“…Peripheral blood mononuclear cells collected from co-infected piglets showed higher expression levels of inflammatory cytokines, TLR2 and TLR4 and reduced levels of CD4, CD8 and MHC-II. It was also shown that PCV-2 disrupted the integrity and decreased mRNA and protein levels of tight junctions in the lungs of co-infected animals [ 99 ]. Although the authors showed a reduced antibody response against S. suis in virus-infected animals, a poorly characterized commercial kit available in China only was used [ 21 ].…”
Section: S Suis and Viral Mixed And/or Co-infectionsmentioning
confidence: 99%
“…According to our previous study, an in vitro tracheal epithelial barrier model was constructed with STEC using polytetrafluoroethylene 3 μM pore-size membrane transwells (Corning, USA) [ 18 ]. Transwells containing STEC were uninfected or infected with HPS4-YC (MOI 100) for 4, 6, 8, 12, 18 and 24 h. The transepithelial electrical resistance (TEER) was measured with a Millicell ERS-2 electrical resistance system (Millipore, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Western blotting was performed to evaluate the reactivity of the purified Omp2 protein. The same method was described in the reference with some modifications ( 25 ). Briefly, the purified Omp2 protein was transferred onto a polyvinylidene fluoride (PVDF) membrane (Millipore Corporation, USA) after being separated by 12% SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%